DESAIN BANGUNAN PENGENDALI SEDIMEN (SABO) PADA SUNGAI RAPAK DALAM SAMARINDA SEBERANG - INDRIANI, UPIE (KURVA S JURNAL MAHASISWA, 2017)
Sediments are materials or fragments of rocks, minerals and dissolved organic materialsand move in the direction of the flow of river water. Sediments can be distinguished into bed loadsand suspended loads. Sabo Dam building is a water construction which functions as anchoring,reservoir and sediment controller that dissolves in the river flow so that the sediment does notinterfere with the performance of the existing DamThe method used in the calculation of SABO building design is referring to Pd.T12-2004-A. Whereas to know the amount of erosion using USLE (Universal Soil Less Equation) method forsedimentation volume using the equation of erosion multiplied by the time of the Sediment ReleaseRatio multiplied by the watershed area.From the calculation results can be concluded that Estimation of sediment volume asmuch as 1,351 tons / year, and obtained high SABO is 3.5 m width is 4.4 m wide and the top widthis 2 m. SABO design stability is safe against bolsters, shear and carrying capacity.